The Hybrid Research Method Used for (Un)Planned Bratislava Examination and Interpretation - Bočková, Monika (Vysoké učení technické v Brně,Fakulta architektury, 2020)
This paper describes the hybrid method used in the (Un)Planned Bratislava research (2019). The city of Bratislava was analysed as a permanently open work consisting of layers of fragmentary built visions. Part of this research was based on the visual interpretation of archive findings in the spatial context. The use of architectural digital tools allowed new complex comprehension of the issue. Various visualisations of selected locations helped to reveal new causalities in the history of their development.
Keywords: Bratislava; urban planning; history; hybrid research method